Industry-specific prevalence and gender disparity of common mental health problems in the UK: A national repetitive cross-sectional study - Chen, Shanquan; Wang, Yuqi (Frontiers in Public Health, 2023)
Aims To evaluate the prevalence and temporal trend of common mental health problems (CMHP) in the UK by industrial classification from 2012-2014 to 2016-2018, meanwhile evaluating corresponding gender disparities. Methods We used data from Health Survey for England. CMPH was judged by 12-item General Health Questionnaire. Industrial classifications were defined using the UK Standard Industrial Classification of Economic Activities. Data were fitted by logistic models. Results In this study, 19,581 participants covering 20 industries were included. 18.8% of participants were screened positive for CMHP in 2016-2018, which significantly increased from 16.0% in 2012-2014 (adjusted OR[AOR]=1.17, 95%CI 1.08-1.27). In 2016-2018, the prevalence of CMHP ranged from 6.2% in the industry of Mining and quarrying to 23.8% in the industry of Accommodation and food service activities. From 2012-2014 to 2016-2018, none of the 20 industries studied experienced significant decreases in the above prevalence, conversely, three industries saw significant increases, including Wholesale and retail trade, repair of motor vehicles and motorcycles (AOR for trend=1.32, 95%CI 1.04-1.67), Construction (AOR for trend =1.66, 95%CI 1.23-2.24), and Other service activities which can’t be classified (AOR for trend =1.94, 95%CI 1.06-3.55). 11 of the 20 industries studied had significant gender disparities against females, with the smallest gap being in the industry of Transport and storage (AOR=1.47, 95%CI 1.09-2.0) and highest in the industry of Arts, entertainment and recreation (AOR=6.19, 95%CI 2.94-13.03). From 2012-2014 to 2016-2018, gender disparities were narrowed only in 2 industries, including Human health and social work activities (AOR for trend = 0.45, 95%CI 0.27-0.74) and Transport and storage (AOR for trend = 0.5, 95%CI 0.27-0.91). Conclusions The prevalence of CMHP has increased and had a wide variation across industries in the UK. There were disparities against females, and the gender disparities have been keeping almost no improvement from 2012-2014 to 2016-2018.